Efektivitas Penghimpunan dan Pendistribusian Dana ZIS Pada Badan Amil Zakat Nasional Kabupaten Bantaeng - Ainun Awaliah; Rahmawati Muin; Trisno Wardy Putra (AT TAWAZUN: Jurnal Ekonomi Islam, 2022)
This study aims to determine how the system of collecting and distributing ZIS funds at BAZNAS Bantaeng Regency, researchers also want to know the effectiveness of collecting and distributing ZIS funds at BAZNAS Bantaeng Regency. This type of research uses descriptive qualitative methods with a phenomenological approach, while the data sources used are primary data and secondary data, further collection methods used are observation, interviews and documentation. The results of this study indicate that the ZIS fund collection system at BAZNAS Bantaeng Regency is divided into two, namely the direct and indirect collection system. Then the distribution system consists of consumptive and productive distribution. Consumptive distribution is divided into two, namely traditional consumptive and creative consumptive, as well as productive distribution which is divided into traditional productive and creative productive. The effectiveness of the collection and distribution of ZIS funds at BAZNAS Bantaeng Regency can not be said to be effective as a whole when viewed from the measurements according to Campbell J.P where effectiveness can be achieved if it achieves program success, target success, satisfaction with the program, input and output levels and overall goals. However, from this fifth measurement, there are still some that have not been achieved because the collection of ZIS funds has not been evenly distributed to all circles of society, so that the collected ZIS funds do not reach the planned target. Then, in terms of the distribution of ZIS, the distribution is more consumptive in nature and the planning for the distribution of ZIS funds has not yet reached its planning target.